Water resources in Central Asia: regional stability or patchy make-up? - Wegerich, Kai (Informa UK Limited, 2011)
This article explores the cooperation after independence on four Central Asian transboundary rivers. The paper shows that, even though the Central Asian states agreed in 1992 to continue with the basic water-sharing principles, new agreements had to be made. New agreements were only made in basins with large-scale water-control infrastructure, which have transboundary significance or are transboundary themselves. The inequitable water allocation between the riparian states has continued and has not triggered new agreements.